Use of Clearfield technology in the sunflower - Kristó, István; Makó, István; Gazdagné Torma, Mária (Acta Agraria Debreceniensis, 2011)
Sunflower is one of the most important cultivated plants in Hungary. We carried out our research in 2009 with eight imidazolinone resistant hybrids and one conventional variety in order to compare the efficiency and selectivity of Clearfield technology to the conventional system. In the trial the Clearfield hybrids were treated by 3,5 l/ha Wing-P (pre) and 1,2 l/ha Pulsar 40 SL(post). The plot of the conventional variety was sprayed by 4,0 l/ha Wing-P and 0,5 l/ha Goal Duplo (pre). Wing-P also had a poor effect because of the lack of rain. Pulsar 40 SL gave an excellent result against the 2-6 leaves of monocotyledonous and the dicotyledonous weeds. Only the well-developed Hibiscus trionum survived the treatment. The combination of Wing-P and the Goal Duplo herbicide provided poor result against the caracteristical weeds of the experimental area because of the lack of rain. Oxifluorfen with contact effect burned the leaves of the sunflower.